A simple and inexpensive laser dissection of fasciculated axons from motor nerve organoids - Ikegami, Yasuhiro; Duenki, Tomoya; Arakaki, Ikuma; Sakai, Ryo; Osaki, Tatsuya; Ashihara, Satoshi; Furushima, Tsuyoshi; Ikeuchi, Yoshiho (Frontiers in Bioengineering and Biotechnology, 2024)
Motor nerve organoids could be generated by culturing a spheroid of motor neurons differentiated from human induced pluripotent stem (iPS) cells within a polydimethylsiloxane (PDMS) chip which guides direction and fasciculation of axons extended from the spheroid. To isolate axon bundles from motor nerve organoids, we developed a rapid laser dissection method based on localized photothermal combustion. By illuminating a blue laser on a black mark on the culture device using a dry-erase marker, we induced highly localized heating near the axon bundles. Moving the laser enabled spatial control over the local heating and severing of axon bundles. This laser dissection requires a black mark, as other colors did not produce the same localized heating effect. A CO2 laser destroyed the tissue and the device and could not be used. With this simple, economical laser dissection technique, we could rapidly collect abundant pure axon samples from motor nerve organoids for biochemical analysis. Extracted axonal proteins and RNA were indistinguishable from manual dissection. This method facilitates efficient axon isolation for further analyses.